Associations between comprehensive dietary composition and kidney stone risk: insights from a nationally representative survey - Li, Bo; Li, Feng; Xie, Xi; Xiang, Chen Hui; Li, Meilin (Frontiers in Nutrition, 2025)
BackgroundThis study aimed to identify key dietary components exhibiting significant associations with risk of kidney stone (KS).MethodsThis is a cross-sectional analysis that included data from the National Health and Nutrition Examination Survey (2007–2020) based on 26,372 qualified individuals, who provided self-reported information regarding KS and dietary composition over two days. The relationship between the risk of KS and dietary composition were evaluated using weighted multivariate logistic regression models and restricted cubic spline (RCS) models.ResultsThrough weighted multivariate logistic regression model, daily consumption of citrus, melons, and berries (OR = 0.81, 95% CI = 0.70–0.93), tomatoes (OR = 0.78, 95% CI = 0.61–0.99), milk (OR = 0.84, 95% CI = 0.78–0.91), total dairy (OR = 0.89, 95% CI = 0.84–0.94), and alcoholic drinks (OR = 0.88, 95% CI = 0.84–0.92) were associated with a lower likelihood of KS development, while daily consumption of added sugars correlated with an elevated probability of KS occurrence (OR = 1.01, 95% CI = 1.00–1.01). Restricted cubic spline analysis found that total fruits, total vegetables, total protein foods, total grains, total dairy, oils, solid fats and added sugars and the risk of KS were in a curvilinear relationship adjusted for age, sex, race, marital status, BMI (body mass index), physical activity in recreational time, smoking status, hypertension, diabetes mellitus (DM). (p overall and p non-linear <0.05).ConclusionThis cross-sectional study elucidates intricate curvilinear associations between dietary components and the risk of KS. The consumption of citrus, melons, berries, tomatoes and milk was associated with a significantly lower risk of KS. Our findings highlight the need for prospective studies to confirm these potential protective relationships.